2013
DOI: 10.5194/nhess-13-1105-2013
|View full text |Cite
|
Sign up to set email alerts
|

Thermal infrared brightness temperature anomalies associated with the Yushu (China) <i>M</i><sub>s</sub> = 7.1 earthquake on 14 April 2010

Abstract: Abstract. The paper presents a wavelet transform method to identify possible seismic brightness temperature anomalies that might be associated with the Yushu (Ms = 7.1) earthquake that occurred in Qinghai province of China on 14 April 2010. Daily infrared data from the Chinese geostationary meteorological satellite FY-2E were used for the period from 1 January 2010 to 31 December 2011 and the spatial region 28.1–38.1° N by 91.7–101.7° E. We find that the wavelet transform is an effective method to analyse time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 18 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…The RPS is then calculated by Fourier transform with a certain time window and sliding window length. On the basis of TOA BT, the RPS approach was used to analyze pre-seismic anomalies, but non-seismic anomalies always appeared (Xie et al, 2013).…”
Section: Methods Based On Wavelet Transformmentioning
confidence: 99%
See 1 more Smart Citation
“…The RPS is then calculated by Fourier transform with a certain time window and sliding window length. On the basis of TOA BT, the RPS approach was used to analyze pre-seismic anomalies, but non-seismic anomalies always appeared (Xie et al, 2013).…”
Section: Methods Based On Wavelet Transformmentioning
confidence: 99%
“…Whether anomalies detected in one earthquake case are general or incidental phenomena is often controversial. One of the general strategies is based on the validation and confutation method for verification (Genzano et al, 2015;Lisi et al, , 2015Xiong et al, 2013). In the validation phase, anomalies associated with earthquakes should be found; however, no anomalies should be confirmed in the confutation phase.…”
Section: Other Methodsmentioning
confidence: 99%
“…The research of Qiang ZJ et al (1994, 1999), for example, showed that there was a good correspondence between the oil and gas accumulation zone and the CTIB anomalous region during the EQ; Colacino and Conte (1993) suggested that the concentration of CH 4 was more than two times higher than the average value in the low‐altitude atmosphere before the EQ, where the concentration of CO 2 was 2.6 times higher than the average value. Through a long period of observation, using the same approaches to the processing of long‐term data, researchers arrived at similar results around the Qinghai–Tibet Plateau (Lu ZQ et al, 2005; Guo WY et al, 2006; Zhang YS et al, 2010; Xiong P et al, 2015; Xie T et al, 2013; Xie T and Ma WY, 2015; Bhardwaj et al, 2017b). They also suggested that the warming effect might be related to seismogenic mechanisms; however, this is relevant only if the geological conditions and basin topography allow the gases to gather, which results in the gases being released to form a CTIB anomaly.…”
Section: Resultsmentioning
confidence: 87%
“…We adopt the same approaches to processing data as those in Xie et al (Xie T et al, 2013; Xie T and Ma WY, 2015) and Lu X et al (2016). The process is divided into the following three steps.…”
Section: Methodsmentioning
confidence: 99%
“…Based on long-term monitoring of the bedrock temperature in the Kangding area, the bedrock temperature was strongly correlated with low-level seismic activity and suggested that the drastic change in the bedrock temperature is caused by the stress adjustment. Properties that affect the temperature response of rocks to changes in stress are critical for understanding temperature anomalies in the crust [60][61][62].…”
Section: Significance Of the Experimental Resultsmentioning
confidence: 99%